The transcription repressor Bach2 is required for maintaining the B-1 cell population by regulating self-renewal - Oh, Seung-Gen; Noh, Jeonghyun; Jang, Eunkyeong; Youn, Jeehee (Frontiers in Immunology, 2025)
B-1 cells are a distinct lineage of tissue-resident B cells with crucial roles in innate immunity and tissue homeostasis. Mature B-1 cell pools are mostly maintained by self-renewal in their peripheral niches, in a process that is largely uncharacterized. Here, we investigated the role of the transcription repressor Bach2 in maintaining the B-1 cell pool. We found that B-1 cell numbers and antibody responses were dramatically reduced in adult mice bearing a B cell-specific Bach2 deletion, although the proportions of B-1 progenitors in early neonatal life were unaffected. Cells taken from the fetal liver or bone marrow of Bach2-deleted mice were defective in reconstituting the B-1 cell pool in the peritonea of Rag2-/- hosts, and peritoneal B-1 cell transplants from adult Bach2-deleted mice failed to sustain their numbers in the host’s peritoneum. The mutant B-1 cells proliferated normally in vivo but were more apoptotic. They also expressed the reduced level of the self-renewal factor Bmi1. These results indicate that Bach2 deficiency does not affect the development of B-1 progenitors in fetal liver and bone marrow but impairs the self-renewal of mature B-1 cells in peripheral tissues, which is caused by increased apoptosis. Thus, this study suggests that a cell-autonomous function of Bach2 is crucial for maintaining a stable population size of B-1 cells in their peripheral niches.